Providing pharmacy services during the coronavirus pandemic in Saudi Arabia (Review) - Alshammari, Saad Khalaf; Alqahtani, Ahmed Masoud; Alotaibi, Ahmed Mazi; Alzahrani, Naif Ahmad; Alzahrani, Emad Ahmed; Alkhulaif, Susan Abdulqader; Alharbi, Waleed Farah; Albraiki, Salem Ahmad; Almuteiri, Awad Ghalab; Alzahrani, Nawaf Ateya (Journal of medical and pharmaceutical sciences, 2023)
On March 2, 2020, the Kingdom of Saudi Arabia confirmed its first case of the emerging coronavirus strain that causes coronavirus disease 2019 (COVID-19). Shortly thereafter, the number of confirmed cases nationwide began to rise. Since the looming outbreak, all healthcare professionals, including pharmacists, began to work at maximum capacity and effort. The Saudi Society of Clinical Pharmacy (SSCP) recognizes the significant impact pharmacists can have during outbreaks. Based on the scientific evidence available during this outbreak, the SSCP set up an expert working group to conceptualize and draft proposed recommendations that highlight the roles and responsibilities of pharmacists during epidemics and pandemics. The SSCP working group made 28 recommendations. In addition to national and institutional guidelines, these recommendations could serve as guidance for affected entities.